The effects of 14-week betaine supplementation on endocrine markers, body composition and anthropometrics in professional youth soccer players: a double blind, randomized, placebo-controlled trial - Nobari, H.; Kargarfard, M.; Minasian, V.; Cholewa, J. M.; Pérez-Gómez, J. (Journal of the International Society of Sports Nutrition, 2021)
Betaine supplementation may enhance body composition outcomes when supplemented chronically during an exercise program. The purpose of this study was to evaluate the effect of betaine supplementation on development-related hormones, body composition, and anthropometrics in professional youth soccer players during a competitive season. Methods: Twenty-nine players (age, 15.45 ± 0.25 years) were matched based upon position and then randomly assigned to a betaine group (2 g/day; n = 14, BG) or placebo group (PG, n = 15). All subjects participated in team practices, conditioning, and games. If a subject did not participate in a game, a conditioning protocol was used to ensure workload was standardized throughout the 14-week season. Growth hormone (GH), insulin-like growth factor-1 (IGF-1), testosterone, cortisol, height, weight, and body composition were assessed at pre-season (P1), mid-season (P2) and post-season (P3). Anthropometric variables were also measured following a one-year follow-up (F). Results: Significant (p < 0.05) group x time interactions were found for testosterone and testosterone to cortisol ratio (T/C). Both variables were greater in BG at P2 and P3 compared to P1, however, the testosterone was less in the PG at P3 compared to P2. There was no significant group by time interactions for GH, IGF-1, lean body mass, or body fat. There was a significant (p < 0.05) group x time interaction in height and weight at F, with the greater increases in BG compared to PG. Conclusion: Betaine supplementation increased testosterone levels and T/C ratio in youth professional soccer players during a competitive season. Betaine supplementation had no negative effects on growth (height and weight) and may attenuate reductions in testosterone due to intense training during puberty.